2017
DOI: 10.1038/s41598-017-13265-8
|View full text |Cite
|
Sign up to set email alerts
|

microRNA profiling in lung tissue and bronchoalveolar lavage of cigarette smoke-exposed mice and in COPD patients: a translational approach

Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by a progressive airflow limitation and is associated with a chronic inflammatory response in both airways and lungs. microRNAs (miRNAs) are often highly conserved between species and have an intricate role within homeostatic conditions and immune responses. Also, miRNAs are dysregulated in smoking-associated diseases. We investigated the miRNA profile of 523 miRNAs by stem-loop RT-qPCR in lung tissue and cell-free bronchoalveolar lavage (BAL) super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 35 publications
6
46
0
Order By: Relevance
“…Specifically, the expression of mmu-miR-21a-5p, mmu-miR-147-3p, mmu-miR-449a-5p, and mmu-miR-703 was deregulated in the lungs of mice exposed to multi-walled carbon nanotubes [24] and mmu-miR-342-3p in mice exposed to nano-TiO2 particles [25]. The deregulation of the miRNAs observed in our study was further found in the lungs of mice after cigarette smoke exposure (mmu-miR-21a-5p, mmu-miR-135b-5p, mmu-miR-146a-5p, mmu-miR-146b-5p, mmu-miR-155-5p, mmu-miR-342-3p, mmu-miR-449a-5p, mmu-miR-489-3p, and mmu-miR-672-5p) [26], in mice with cigarette smoke induced atherosclerosis (mmu-miR-21a-5p and mmu-miR-155-5p) [27], in the lungs of mice after radon inhalation (mmu-miR-21a-3p, mmu-miR-135b-5p, mmu-miR-146b-5p, mmu-miR-1298-5p, mmu-miR-6972-5p, and mmu-miR-703) [28], in mice with lung tumors (mmu-miR-135b-5p, mmu-miR-146b-5p, mmu-miR-223-3p, and mmu-miR-1298-5p) [29][30][31], in an ovalbumin-induced asthma mouse model (mmu-miR-21a-5p, mmu-miR-135b-5p, mmu-miR-146a-5p, mmu-miR-155-5p, mmu-miR-223-3p, and mmu-miR-451a) [32], and in mice with pneumonia and influenza infections (mmu-miR-21a-5p, mmu-miR-144-5p, mmu-miR-155-5p, and mmu-miR-223-3p) [33][34][35]. This overall suggests that the inhalation of CuO NPs induces a similar response as the above-mentioned adverse conditions and therefore likely has negative effects on the organism.…”
Section: Discussionsupporting
confidence: 65%
“…Specifically, the expression of mmu-miR-21a-5p, mmu-miR-147-3p, mmu-miR-449a-5p, and mmu-miR-703 was deregulated in the lungs of mice exposed to multi-walled carbon nanotubes [24] and mmu-miR-342-3p in mice exposed to nano-TiO2 particles [25]. The deregulation of the miRNAs observed in our study was further found in the lungs of mice after cigarette smoke exposure (mmu-miR-21a-5p, mmu-miR-135b-5p, mmu-miR-146a-5p, mmu-miR-146b-5p, mmu-miR-155-5p, mmu-miR-342-3p, mmu-miR-449a-5p, mmu-miR-489-3p, and mmu-miR-672-5p) [26], in mice with cigarette smoke induced atherosclerosis (mmu-miR-21a-5p and mmu-miR-155-5p) [27], in the lungs of mice after radon inhalation (mmu-miR-21a-3p, mmu-miR-135b-5p, mmu-miR-146b-5p, mmu-miR-1298-5p, mmu-miR-6972-5p, and mmu-miR-703) [28], in mice with lung tumors (mmu-miR-135b-5p, mmu-miR-146b-5p, mmu-miR-223-3p, and mmu-miR-1298-5p) [29][30][31], in an ovalbumin-induced asthma mouse model (mmu-miR-21a-5p, mmu-miR-135b-5p, mmu-miR-146a-5p, mmu-miR-155-5p, mmu-miR-223-3p, and mmu-miR-451a) [32], and in mice with pneumonia and influenza infections (mmu-miR-21a-5p, mmu-miR-144-5p, mmu-miR-155-5p, and mmu-miR-223-3p) [33][34][35]. This overall suggests that the inhalation of CuO NPs induces a similar response as the above-mentioned adverse conditions and therefore likely has negative effects on the organism.…”
Section: Discussionsupporting
confidence: 65%
“…Increased expression resulted from Nrf-2 displacement of repressive factors [BTB and CNC homology 1, basic leucine zipper transcription factor (Bach1) and v-Maf avian musculoaponeurotic fibrosarcoma oncogene homolog K (MafK) heterodimers] binding to an upstream antioxidant response element, resulting in increased CFTR transcription (248). However, over time, CFTR mRNA stability decreased due to upregulation of specific oxidative stress-induced mi-croRNAs (e.g., miR-223, miR-155, and miR-21) targeting CFTR transcripts (15,34,96,214).…”
Section: Cftr and Anion Secretionmentioning
confidence: 99%
“…113,114,138,147 miR-218 and miR-22 were elevated in MS and EAE to levels similar to those found in cigarette smokers. 116,117,129,153 Survivin expressions in MS (4.5-fold) could not be attributed to cigarette smoking only (1.79-fold). 125,144 Levels of Let-7c in MS did not correlate with those found in cigarette smokers (-1.45-fold).…”
Section: Data Extractionmentioning
confidence: 89%
“…170 Furthermore, as detailed previously, miR-155 was associated with MS and MS environmental stimuli (Table 2). 108,110,116,121,130,145,235 Likewise, Ehtesham et al demonstrated that IFN-β can restore the expression levels of the previously described MS-or EAE-associated miRNAs: miR-145 and miR-20a (Tables 2 and 5). 24,122,138,171,234,241,260 Similarly, Manna et al studied 16 differentially expressed miRNAs in IFN-β treated RRMS patients vs naive patients.…”
Section: Data Extractionmentioning
confidence: 91%
See 1 more Smart Citation